Brenda Is in the Room & Other Poems. - Teicher, Craig Morgan, 1979- (University Press of Colorado, 2007)
The winner of the 2007 Colorado Prize for Poetry, this is a beautiful and original work that appears to be, on first impression, a light-hearted and amusingly self-conscious account of daily life, but reminds us that our mundane lives are utterly strange and magical.